IMPLEMENTASI MAGANG PEMONDOKAN MAHASISWA UIN ANTASARI BANJARMASIN - Sari, Nyai Rukmana (Program Studi PAI STAI Al Falah Banjarbaru, 2022)
ABSTRACT: The boarding internship is a program held by the Department of Islamic Religious Education at one of the well-known campuses in the city of Banjarmasin, namely UIN Antasari Banjarmasin. This boarding internship is one solution that is held for PAI students who are still lacking in reading skills (Qiraat, Tahsin, Tajwid) and writing the Qur'an. This study aims to describe the implementation of student boarding internships at the Department of Islamic Education, Faculty of Tarbiyah and Teacher Training at UIN Aantasari Banjarmasin 2016 from planning, implementation, as well as evaluation. In this study, the authors also want to know the supporting and inhibiting factors in the internship program. This study uses qualitative (field) research that is oriented or looks at the state of natural phenomena or symptoms. The research was conducted at the Al-Hikmah Islamic Boarding School in Kelayan A. The subjects were 2 program managers and 20 students of the 2016 Islamic Religious Education Department. The data collected by the researchers were observation, interviews and documentation. While in data processing used collection techniques, data editing and interpretation. The results showed (1) The application of student boarding internships went well, this was shown by careful planning, starting from testing PAI students by tahsin lecturers, recitation of the Qur'an in the course